2016
DOI: 10.1126/science.aaf8625
|View full text |Cite
|
Sign up to set email alerts
|

Response to Comment on “A bacterium that degrades and assimilates poly(ethylene terephthalate)”

Abstract: Yang et al. suggest that the use of low-crystallinity poly(ethylene terephthalate) (PET) exaggerates our results. However, the primary focus of our study was identifying an organism capable of the biological degradation and assimilation of PET, regardless of its crystallinity. We provide additional PET depolymerization data that further support several other lines of data showing PET assimilation by growing cells of Ideonella sakaiensis. W e appreciate the Comment by Yang et al.(1) and are grateful for this op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 13 publications
1
37
0
Order By: Relevance
“…For instance, the preference of this system for p ‐nitrophenol (pNP)‐linked aliphatic esters is lower than that of TfH, LCC, and FsC, but in terms of PET films, the ability of the PETase/MHETase system is 120, 5.5, and 88 times higher than that of TfH, LCC, and FsC, respectively . Essentially, PETase shows better performance on highly crystallized PET, commonly regarded as a knotty polymer for hydrolysis, than other enzymes …”
Section: Figurementioning
confidence: 99%
“…For instance, the preference of this system for p ‐nitrophenol (pNP)‐linked aliphatic esters is lower than that of TfH, LCC, and FsC, but in terms of PET films, the ability of the PETase/MHETase system is 120, 5.5, and 88 times higher than that of TfH, LCC, and FsC, respectively . Essentially, PETase shows better performance on highly crystallized PET, commonly regarded as a knotty polymer for hydrolysis, than other enzymes …”
Section: Figurementioning
confidence: 99%
“…Recently, a new bacterial species, Ideonella sakaiensis , which can use PET as a carbon source, was isolated 17 20 . The PETase of I. sakaiensis ( Is PETase) can degrade PET at a moderate temperature (30 °C) and has relatively higher activity than other PET-degrading enzymes, such as cutinases and lipases 17 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] For example, cutinases from Thermobifida fusca [8,9] and the most efficient PET hydrolyzing esterase, leaf and branch compost cutinase( LCC). [12][13][14][15][16][17][18][19][20] Although PETase is highly specific to PET,t he enzymes hows poor catalytic activity and is difficult to use in industrial processes. [12][13][14][15][16][17][18][19][20] Although PETase is highly specific to PET,t he enzymes hows poor catalytic activity and is difficult to use in industrial processes.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] In 2016, our research group also identified aP ET-specific hydrolase (PETase, EC: 3.1.1.101, PDBID:5 XJH) from the PET assimilating bacterium, Ideonella sakaiensis (Figure1b). [12][13][14][15][16][17][18][19][20] Although PETase is highly specific to PET,t he enzymes hows poor catalytic activity and is difficult to use in industrial processes. [12] In 2013, Espino-Rammer et al reported an interesting approach to accelerate the catalytic activityo fP ET hydrolyzing enzyme Humicola insolens cutinase (HiC) by using additives.…”
Section: Introductionmentioning
confidence: 99%